Standing waves of the stepped dropshaft in a deep tunnel stormwater system - Sun, Jingkang (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
The deep tunnel stormwater system, consisting of dropshafts and underground tunnels, is used to alleviate or prevent urban water problems associated with extreme rainfall events. The stepped dropshaft can transport surface runoff to the tunnels with high energy dissipation, low risk of cavitation and good exhaust performance, which well meets the requirement of the deep tunnel stormwater system. In the present study, the characteristics of the standing wave were investigated by experiments and numerical simulations, including the peak, trough and length of the standing wave. The flow regimes were divided into the nappe flow, the transition flow and the skimming flow with the increase of discharge, in which the standing wave mainly occurs on the external wall under the nappe flow and the transition flow. Influences of inflow discharge and dropshaft geometries were analyzed, including step rotation angle, relative step height and dropshaft curvature. The relations of the characteristics of standing wave with these effect factors were obtained. The maximum discharge capacity of the stepped dropshaft was established by considering that the standing wave just reached the above steps, which could be useful for the design and safe operation of the stepped dropshaft